24-Hydroxycholesterol Induces Tau Proteasome-Dependent Degradation via the SIRT1/PGC1α/Nrf2 Pathway: A Potential Mechanism to Counteract Alzheimer's Disease - Gabriella Testa; Serena Giannelli; Barbara Sottero; Erica Staurenghi; Giorgio Giaccone; Paola Caroppo; Paola Gamba; Gabriella Leonarduzzi (MDPI AG, 2023)
Considerable evidence indicates that cholesterol oxidation products, named oxysterols, play a key role in several events involved in Alzheimer's disease (AD) pathogenesis. Although the majority of oxysterols causes neuron dysfunction and degeneration, 24-hydroxycholesterol (24-OHC) has recently been thought to be neuroprotective also. The present study aimed at supporting this concept by exploring, in SK-N-BE neuroblastoma cells, whether 24-OHC affected the neuroprotective SIRT1/PGC1α/Nrf2 axis. We demonstrated that 24-OHC, through the up-regulation of the deacetylase SIRT1, was able to increase both PGC1α and Nrf2 expression and protein levels, as well as Nrf2 nuclear translocation. By acting on this neuroprotective pathway, 24-OHC favors tau protein clearance by triggering tau ubiquitination and subsequently its degradation through the ubiquitin-proteasome system. We also observed a modulation of SIRT1, PGC1α, and Nrf2 expression and synthesis in the brain of AD patients with the progression of the disease, suggesting their potential role in neuroprotection. These findings suggest that 24-OHC contributes to tau degradation through the up-regulation of the SIRT1/PGC1α/Nrf2 axis. Overall, the evidence points out the importance of avoiding 24-OHC loss, which can occur in the AD brain, and of limiting SIRT1, PGC1α, and Nrf2 deregulation in order to prevent the neurotoxic accumulation of hyperphosphorylated tau and counteract neurodegeneration.